Low efficacy of levamisole for Ascaridia galli control in experimentally infected poultry: first report in Cajamarca (Peru). - Zavala, D. (2025)
Chickens play an essential role in the global economy and household nutrition. The farming system, particularly extensive or backyard production, affects their productivity due to intestinal parasites, with Ascaridia galli being the most prevalent. Various active compounds are utilized to mitigate its impact; however, improper administration frequently leads to resistant parasites. In some instances, efficacy assessments are not conducted, leaving the effectiveness of different drugs uncertain. This study aimed to evaluate the clinical and controlled efficacy of levamisole in poultry experimentally infected with A. galli in Cajamarca, Peru. Thirty Gallus gallus domesticus chicks were experimentally infected with 210 embryonated A. galli eggs. After confirming established infection through weekly fecal egg counts, 20 birds with ≥ 100 EPG were selected and randomly assigned to control (n = 10) and treatment (n = 10) groups. The treatment group received a single oral dose of levamisole (30 mg/kg body weight). Efficacy was determined by calculating the percentage reduction in egg counts and adult worm burden at day 7 post-treatment. The clinical efficacy between the control and treatment groups was 81.25% (95% CI: 79.63-82.87), the clinical efficacy between pre- and post-treatment was 79.61% (95% CI: 77.87-81.35), and the controlled efficacy was 71.07% (95% CI: 55.74-88.40). No statistically significant differences were observed between the formulas used to determine clinical efficacy (P > 0.01). In conclusion, levamisole administered at 30 mg/kg was insufficiently effective against A. galli in poultry under experimental conditions in Cajamarca, suggesting potential resistance and the need for alternative control strategies.